Divergência e controle genético de caracteres de produção e qualidade de fibra do algodão colorido - Cunha Neto, Jonas (2014)
Cotton is the most important textile fiber in the world. Among all cotton cultivars released, those with naturally colored fiber has been of great importance as a raw material for the textile industry, mainly to meet demands for ecological and organic fabrics. In this sense, the aim of this study was identify genotypes of colored cotton fiber with good yield and fiber quality. The specific objectives were identify contrasting genotypes that can be used in breeding of colored cotton and also identify gene actions that are involved in the performance of the hybrids formed by crossing between four cultivars of colored fiber with six traditional cultivars of white fiber. In the first stage of the research it was conducted studies over genetic diversity in the parents used by univariate and multivariate techniques, and in the second step, we estimated effects of general combining ability ( GCA) and specific combining ability (SCA ), identifying the types of gene actions involved in the control of the observed features, using the methodology REML/BLUP. The statistical design used in the experimental data was randomized block with 24 treatments (14 hybrids and 10 parents), spaced 1,25 m between rows and 0,25 between plants and five plants per plot. They were collected samples from 20 bolls from each treatment used to evaluate 12 technological characteristics of the fiber in HVI. The most divergent cultivars, involving different groups, was between the BRS Verde and BRS Buriti, followed by BRS 293 and BRS. Smaller distances were obtained between cultivars of white fiber. Highlight for BRS 286 and BRS 293 cultivar. The features CSP,% FIB, PAC and PAP were more important for the genetic divergence between the parents. Additive genetic effects are more important for the genetic control of the characteristics of production and quality of cotton fibers.